Remembering 1919: The Winnipeg General Strike - Thiessen, Janis (Labour / Le Travail, 2020)
Despite an abundance of research on the Winnipeg General Strike of 1919, how the strike has been remembered and commemorated by subsequent generations of Winnipeggers has been understudied. Though many archived oral histories of those involved in the strike exist, the intergenerational memory of the strike has been largely unaddressed. In anticipation of the strike’s centennial, I conducted oral history interviews with six descendants of those involved in the 1919 strike, to learn how stories of the strike have been passed down in their families and how those stories shaped the interviewees’ own understandings of labour and social justice. These interviews, though limited in number, attest to the importance of memory (both individual and collective) in oral history and, subsequently, in labour history.